2007
DOI: 10.1111/j.1600-0668.2006.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and prediction of indoor air quality using a breathing thermal manikin

Abstract: Recommendations for optimal simulation of human breathing by means of a breathing thermal manikin when studying pollution concentration, temperature and humidity of the inhaled air as well as the transport of exhaled air (which may carry infectious agents) between occupants are outlined. In order to compare results obtained with breathing thermal manikins, their nose and mouth geometry should be standardized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 12 publications
5
84
1
2
Order By: Relevance
“…For both cases the magnitude of peak AQI was relatively unaffected by changing the strength of the thermal plume. This is in contrast to Melikov and Kaczmarczyk [12], who have shown that the clothing insulation can significantly affect the air quality in the BZ. This discrepancy can be explained by how the measurement of air quality was taken in the experiment conducted by Melikov and Kaczmarczyk, who recorded the air quality only at a single fixed point and made no adjustment to the nozzle angle, which could miss the peak value.…”
Section: Effect Of the Strength Of The Thermal Plume (Clothing)contrasting
confidence: 67%
See 1 more Smart Citation
“…For both cases the magnitude of peak AQI was relatively unaffected by changing the strength of the thermal plume. This is in contrast to Melikov and Kaczmarczyk [12], who have shown that the clothing insulation can significantly affect the air quality in the BZ. This discrepancy can be explained by how the measurement of air quality was taken in the experiment conducted by Melikov and Kaczmarczyk, who recorded the air quality only at a single fixed point and made no adjustment to the nozzle angle, which could miss the peak value.…”
Section: Effect Of the Strength Of The Thermal Plume (Clothing)contrasting
confidence: 67%
“…The degree of entrainment is in turn affected by the design and exit conditions of the PV nozzle and general ventilation diffuser, and by the location of the PV nozzle and general ventilation diffuser relative to the person. While numerous experimental investigations of these factors have been carried out and yielded invaluable insights into the performance of a variety of PV configurations under a wide range of scenarios [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], the design of an effective PV system can be considerably advanced by employing validated, high-fidelity CFD techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The mouth of the manikin was slightly open, with an ellipsoidal opening with a cross-sectional area of 158 mm 2 . Jets emerging from the nostrils were deflected 40° downwards from the horizontal [25]. the manikin's body.…”
Section: Introductionmentioning
confidence: 99%
“…Practically, the spatial distribution of aerosol pollutants in close proximity to an occupant may be affected by the thermal boundary layer around a human body, occupant movement and breathing, and the overall airflow pattern in a space (Rim and Novoselac, 2009). The human's respiratory activities most likely affect the local airflow distribution and transport of contaminants from occupants' exhalation (Björn and Nielsen, 2002;Melikov et al, 2002Melikov et al, , 2007. It has been reported that airflow patterns can be very important regarding indoor pollutant transmission (Pantelic et al, 2009;Bolashikov et al, 2012;Pantelic and Tham, 2013).…”
Section: Introductionmentioning
confidence: 99%